Arthrogryposis Multiplex Congenita: Case Report - Ayla Aktulay; Saliha Sağnıç; Özlem Moraloğlu Tekin; Yaprak Engin Üstün; Elif Gül Yapar Eyi; Leyla Mollamahmutoğlu (Medical Network, 2016)
Arthrogryposis multiplex congenita (AMC), characterized by multiple congenital joint contractures due to decreased fetal movements, is a non-progressive rare syndrome. Prevalence is determined to be 1 in 3000 deliveries. Although it is autosomal recessively inherited, sporadic cases have also been reported. Prenatal diagnosis of AMC is difficult. Here we report a case with a diagnosis of AMC not diagnosed during antenatal follow-up.